Meta-analysis of video-assisted versus open parathyroidectomy for primary hyperparathyroidism. (November 2015) - Abd Elwahab, Sami M; Lowery, Aoife J; O'Brien, Kirsty; Redmond, Henry P
The gold standard treatment of primary hyperparathyroidism was bilateral neck exploration. Video-assisted parathyroidectomy (VAP) facilitated less invasive surgery, however there is lack of evidence comparing it to open parathyroidectomy (OP). A meta-analysis was conducted according to the PRISMA guidelines to compare them. In three eligible randomized controlled trials (241 patients), VAP operative time (61.7 ± 12 min) was comparable to OP (59.9 ± 6 min), less early postoperative pain, higher cosmetic satisfaction (statistically not significant) and 4% failure rate (none in OP). 25% of VAP converted to OP. Hypocalcaemia was six-times less in VAP (RR 6.4). Careful patient selection and unequivocally positive preoperative localization are critical to the success of this procedure. To our knowledge, this is the first meta-analysis comparing the two techniques.